2008
DOI: 10.7227/ijeee.45.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Field of a Rotating Cylindrical Magnet

Abstract: The source of each component of a magnetic fi eld is always a material object. If it moves, it can be treated as carrying its fi eld with it. Also, by applying Maxwell's equations to relevant situations, it is argued that the fi eld of a rotating cylindrical magnet does rotate with the magnet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…is why the opposite point of view is sometimes termed 'the bristle theory', whose adherents [18][19][20][21][22][23] believe in the rotation of the magnetic field with the rotating magnet. As for every solid body, the magnetic field possesses a mass energy (with a density proportional to B 2 ) concentrated in a certain domain of space.…”
Section: The Unipolar Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…is why the opposite point of view is sometimes termed 'the bristle theory', whose adherents [18][19][20][21][22][23] believe in the rotation of the magnetic field with the rotating magnet. As for every solid body, the magnetic field possesses a mass energy (with a density proportional to B 2 ) concentrated in a certain domain of space.…”
Section: The Unipolar Generatormentioning
confidence: 99%
“…He also concluded that the rotating magnetic field was a physical reality. More recently, Rajaraman [21] presented good arguments in favour of the effect of the moving field view: 'the moving field theory or bristle theory is not only simpler, but also more logical, more consistent and more economical'. He proposed that quantitative experiments should be carried out but was apparently unaware of previous work [19,22,23].…”
Section: Previous Experimental Workmentioning
confidence: 99%
“…More than a century after Lodge this topic remained a subject for controversy between eminent physicists with some Nobel laureates included (Leus & Zatolokin, 2006). Hitherto some highly sophisticated experiments have been suggested and tried (Zajev & Dokuchajev, 1964;Bogach, 1996;Kelly, 2004;Rajaraman, 2008;Leus & Taylor, 2011;, which confirmed the correctness of Lodge's view.…”
Section: The Role Of Vector Potential In Electromagnetic Transmissionmentioning
confidence: 88%
“…. the moving field theory or bristle theory is not only simpler, but also more logical, more consistent and more economical' [3].…”
Section: Magnetic Dipole Moving Through a Circular Loopmentioning
confidence: 99%